Aqueous nickel-iron battery and preparation method thereof

High-resolution metal structure electrodes are prepared through DLP technology and an ordered three-dimensional porous structure is designed, which solves the problem of slow transmission rate of traditional 3D porous structures and achieves efficient electrochemical performance and sustainable production.

CN114883669BActive Publication Date: 2025-02-25NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210384815.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-13
Publication Date
2025-02-25
Estimated Expiration
2042-04-13

AI Technical Summary

Technical Problem

The electron/ion transmission rate of traditional 3D porous structures is slow, and the existing metal 3D printing technology is costly and has limited resolution, making it difficult to achieve efficient and sustainable battery manufacturing.

Method used

Digital light treatment (DLP) technology is used to prepare high-resolution, layered porosity, fully metal structure electrodes, reduce material limitations through acid/salt-assisted reactions, and design an orderly three-dimensional periodic porous structure to ensure the electron/ion transmission path. Determinism.

Benefits of technology

It realizes efficient electron/ion transmission, improves electrochemical and mechanical properties, reduces production costs, and is easy to recycle raw materials, supporting sustainable production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114883669B_ABST
    Figure CN114883669B_ABST
Patent Text Reader

Abstract

The present invention discloses an aqueous nickel-iron battery and a preparation method thereof, belonging to the field of batteries; the battery comprises a Fe2O3@3DFe positive electrode, a NiCo2S4@3DNi negative electrode and a potassium hydroxide solution electrolyte; the preparation method comprises first designing an F‑KS structural template by software, then respectively preparing a NiCo2S4@3DNi electrode and a Fe2O3@3DFe electrode using a nickel sulfate template and an iron sulfate substrate, and finally assembling the two electrodes in combination with an electrolyte to obtain an aqueous nickel-iron battery. The present invention adopts an aqueous nickel-iron battery composed of porous metal structure electrodes prepared by 3D printing of recyclable metal salts, and deterministically manufactures an ordered electron / ion transmission path by rationally designing electrodes of a three-dimensional periodic porous structure, thereby solving the problem of slow electron / ion transmission rate of the random disorder of the traditional 3D porous structure. At the same time, the raw materials of the process are easy to recycle, which is a good choice for achieving sustainable production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to an aqueous nickel-iron battery and a preparation method thereof. Background Art

[0002] The growing demand for portable devices requires electrochemical storage devices with higher power density, higher energy density, and longer cycle life. In the past few decades, the rapid development of nanostructured electrode materials has enabled the realization of excellent energy or power density. However, their good performance is usually achieved by using nanostructured electrode materials with low mass loading (≤1 mg cm -2 ) but such electrodes are difficult to commercialize.

[0003] Thick electrode design is an effective way to increase the electrode active material loading and thus the device energy density. However, in traditional electrode structures such as sandwich structures, increasing the electrode thickness limits ion diffusion, resulting in high resistance, slower kinetics, and poor rate performance. However, 3D structured electrodes can overcome these limitations. The interconnected channel network combined with hierarchical pores ensures efficient charge transport throughout the electrode volume, enabling fast and high-capacity energy storage.

[0004] A large number of strategies have been developed to prepare porous metals, such as chemically routed directed self-assembly, gas injection, dealloying, and investment casting. These methods are of great significance in the commercialization of metal products, but they also have some disadvantages, such as cumbersome steps, low yield, uncontrollable feature size, and poor strength in producing complex geometric structures. In addition, there is a growing focus on the sustainability of recycling technologies and processes. Electrodes / catalysts with scrap metals / metal compounds are currently recycled in an unsafe and non-environmentally friendly manner, so there are currently great efforts to address this limitation to achieve sustainable closed-loop manufacturing of batteries.

[0005] Advances in additive manufacturing (AM), also known as 3D printing, offer new possibilities to address these challenges in metal processing. Due to the randomness of conventional 3D porous metal structures, electron / ion transport rates remain unsatisfactory. In stark contrast, 3D printed metal structures allow for deterministic and finely crafted ordered electron / ion transport pathways. Designed and optimized physical structures of electrode structures can achieve the goal of directly increasing active material loading, resulting in better electrochemical performance. Currently, the most mature metal 3D printing technologies are selective laser melting (SLM) and electron beam melting (EBM) methods, but these technologies are prohibitively expensive and their resolution is still limited. Digital light processing (DLP) technology is a powerful and widely used 3D printing method that uses photopolymerization for 3D printing, which can be built much faster than traditional stereolithography equipment and can achieve high-resolution, complex geometry printing. It has low cost, simple operation, fast manufacturing speed, high material usage efficiency, high resolution, and the ability to print complex 3D structures. If properly utilized in the field of energy storage, it is very promising. However, the samples prepared by the DLP method are usually polymers. Common methods for obtaining conductive metal substrates by DLP include: using the printed polymer parts as templates and metallizing the samples by chemical vapor deposition (CVD), physical vapor deposition (PVD), electroless plating or electrodeposition.

[0006] In this work, we report a method to produce fully metallic structures with high resolution and hierarchical porosity via DLP without metallization. The material limitations of DLP metal printing are reduced by using metal salts as precursors followed by a simple chemical process (acid / salt-assisted reaction). The raw materials of this process are both cost-effective and easily recyclable, a dual advantage for sustainable production. Summary of the invention

[0007] Technical issues to be solved:

[0008] In order to avoid the shortcomings of the prior art, the present invention provides an aqueous nickel-iron battery and a preparation method thereof, which uses an aqueous nickel-iron battery composed of porous metal structure electrodes prepared by 3D printing of recyclable metal salts, and through the reasonable design of electrodes with three-dimensional periodic porous structures, deterministically manufactures orderly electron / ion transmission paths, solving the problem of slow electron / ion transmission rate due to random disorder of traditional 3D porous structures. At the same time, the raw materials of this process are easy to recycle, which is a good choice for achieving sustainable production.

[0009] The technical solution of the present invention is: an aqueous nickel-iron battery, comprising a positive electrode, a negative electrode and an electrolyte; characterized in that: the positive electrode is Fe2O3@3DFe, the negative electrode is NiCo2S4@3DNi, and the electrolyte is a potassium hydroxide solution.

[0010] A further technical solution of the present invention is that the positive electrode and the negative electrode are layered porous 3D metal nickel electrodes.

[0011] A method for preparing an aqueous nickel-iron battery, characterized in that the specific steps are as follows:

[0012] Step 1: Design the F-KS structure template through software;

[0013] A certain proportion of nickel sulfate powder, Variquat CC 42NS, and a light-curable resin are mixed, stirred, and ground to obtain a resin, and the resin is used for printing; after printing, the printed structure is removed from the printing platform, ultrasonically cleaned for multiple times, and dried at room temperature to obtain a nickel sulfate template;

[0014] A certain proportion of ferric sulfate powder, Variquat CC 42NS, and a light-curable resin are mixed, stirred, and ground to obtain a resin, and the resin is used for printing; after printing, the printed structure is removed from the printing platform, ultrasonically cleaned for multiple times, and dried at room temperature to obtain a ferric sulfate substrate;

[0015] Step 2: The nickel sulfate template / iron sulfate substrate obtained in step 1 is placed in a muffle furnace for degreasing and sintering, and the degreased nickel oxide structure / iron oxide structure is then transferred to a PECVD furnace and heated and reduced in an argon-hydrogen mixed atmosphere to obtain a 3D printed metal nickel structure / 3D printed metal iron structure;

[0016] Step 3: Dissolve a certain amount of cobalt nitrate hexahydrate, nickel nitrate hexahydrate and hexamethylenetetramine in methanol and stir to form a transparent pink solution; transfer the solution to an autoclave lined with polytetrafluoroethylene, and then suspend the 3D printed metal nickel structure obtained in step 2 in the solution, and heat it to synthesize Ni-Co LDH; then wash it with deionized water several times and dry it in a vacuum oven to obtain Ni-Co LDH@3DNi;

[0017] Step 4: Add a certain amount of sodium sulfide nonahydrate into deionized water and stir until transparent; then put the Ni-Co LDH@3DNi sample prepared in step 3 into the above transparent solution to obtain a mixture; then, transfer the obtained mixture to an autoclave lined with polytetrafluoroethylene, heat the reaction, take out the product, wash it with deionized water, and dry it to obtain a NiCo2S4@3DNi electrode;

[0018] Step 5: Mix a certain amount of sodium hydroxide, ammonium persulfate, deionized water and ammonium fluoride solution, and transfer them to an autoclave lined with polytetrafluoroethylene; immerse the 3D printed metal iron structure in the solution of the autoclave in this step; take it out after heating reaction, rinse it with deionized water and dry it in a vacuum oven; heat the prepared substrate and keep it in an Ar atmosphere to obtain a Fe2O3@3DFe electrode;

[0019] Step 6: Use Fe2O3@3DFe as the positive electrode, NiCo2S4@3DNi as the negative electrode, and 6M potassium hydroxide as the electrolyte to assemble an aqueous nickel-iron battery.

[0020] A further technical solution of the present invention is: in the step 1, 20-60g of metal salt, 1-10mL of Variquat CC42NS, and 30mL of photocurable resin are mixed in an amber bottle, stirred for 1-3 hours in a magnetic stirrer at room temperature, and then ground with a planetary ball mill; the photocurable resin is prepared by adding 2wt.% TPO to E-HDDA and E-TMPTA in a ratio of 3:22.

[0021] A further technical solution of the present invention is: in the step 2, the sintering temperature of the degreasing sintering process is 200-1000°C, and the sintering time is 1-5 hours; the reduction step is reduction in an argon-hydrogen mixed atmosphere at 400-900°C for 1-5 hours.

[0022] A further technical solution of the present invention is: in the step 3, the cobalt nitrate hexahydrate is 0.03-0.1g, the nickel nitrate hexahydrate is 0.01-0.5g, the hexamethylenetetramine is 0.05-0.1g, and the methanol is 20-50mL; the autoclave temperature is 150-200°C, and the reaction time is 10-20 hours; the vacuum drying temperature is 40-80°C, and the time is 10-20 hours.

[0023] A further technical solution of the present invention is: in the step 4, the amount of sodium sulfide nonahydrate is 0.5-1.0 g, the amount of deionized water is 10-50 mL, the temperature of the autoclave is 100-150° C., the reaction time is 5-10 hours, the drying temperature is 40-80° C., and the reaction time is 10-20 hours.

[0024] A further technical solution of the present invention is: in the step 5, the sodium hydroxide is 0.1-0.5 g, the ammonium persulfate is 0.2-0.6 g, the deionized water is 10-40 mL, the 50 mM ammonium fluoride solution is 1.0-6.0 mL, the autoclave temperature is 100-200 ° C, the reaction time is 10-20 hours, the vacuum drying temperature is 200-400 ° C, the heating rate is 1 ° C / min, and it is maintained in an Ar atmosphere for 2-6 hours.

[0025] A further technical solution of the present invention is: in step six, the Fe2O3@3DFe and NiCo2S4@3DNi electrodes are immersed in an electrolyte, placed at room temperature, assembled face to face and immersed in the solution to assemble an aqueous nickel-iron battery.

[0026] Beneficial Effects

[0027] The beneficial effects of the present invention are as follows: the present invention provides an aqueous nickel-iron battery composed of porous metal structure electrodes prepared by 3D printing of recyclable metal salts and a preparation method thereof, firstly combining digital light processing (DLP) technology (a 3D printing technology with a layer resolution of 27 μm) with post-processing and heat treatment to obtain an ordered hierarchical porous 3D metal substrate. This 3D metal structure with an ordered internal structure increases the specific surface area, creates an ordered electron / ion transmission path, and improves the electrochemical performance.

[0028] Excellent mechanical properties: Through systematic finite element analysis and quasi-static compression tests, the metal nickel structure prepared by 3D printing can achieve a compressive strength of 13.52MPa, while the foamed nickel only reaches 0.414Mpa.

[0029] Excellent electrochemical performance: Compared with traditional nickel foam and iron foam, 3D printed nickel and iron substrates have lower resistivity. Based on the 3D printed metal nickel structure, a high active material mass loading capacity (18.38 mg / cm at 4 mm thickness) was prepared. 2 ), high area capacity (44.85mA cm -2 The current density is 7.327 mAh cm -2 ), the current density is from 42.9mAcm -2 Increased to 171.4 mA cm -2 The NiCo2S4@3DNi electrode with a rate performance of 57.28% was prepared based on the 3D printed metal iron structure at 16.02 mA cm -2 The current density is 10.87 mAh cm -2 The Fe2O3@3DFe electrode with high area capacity was used to assemble an asymmetric aqueous nickel-iron battery with a high charge / discharge rate of 16.02 mA cm -2 An impressive current density of 10.87 mAh cm was achieved. -2 Area capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the 3D printed metal nickel substrate.

[0031] Figure 2 This is the scanning electron microscope image of NiCo2S4@3D Ni electrode.

[0032] Figure 3 This is a scanning electron microscope image of the 3D printed metal iron substrate.

[0033] Figure 4 This is the scanning electron microscope image of the Fe2O3@3DFe electrode. DETAILED DESCRIPTION

[0034] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0035] An embodiment of the present invention provides an aqueous nickel-iron battery assembled from 3D structured metal electrodes made by 3D printing using recyclable metal salts as raw materials, including a positive electrode, a negative electrode and an electrolyte; the positive electrode is Fe2O3@3DFe, the negative electrode is NiCo2S4@3DNi, and the electrolyte is a potassium hydroxide solution; the positive electrode and the negative electrode are layered porous 3D metal nickel electrodes.

[0036] In an embodiment of the present invention, a method for preparing an aqueous nickel-iron battery assembled from a 3D structured metal electrode made by 3D printing using a recyclable metal salt as a raw material is provided, and the specific steps are as follows:

[0037] Step 1: Design the “F-KS” structure template using MS Lattice software;

[0038] A certain proportion of nickel sulfate powder, Variquat CC 42NS, and light-curable resin were mixed, stirred, and ground. The obtained resin was printed by an Asiga MAX X27 UV printer (UV wavelength 385nm, layer resolution 27μm); after printing, the printed structure was removed from the printing platform, immersed in IPA for ultrasonic cleaning 3 times, and then dried at room temperature to obtain a nickel sulfate template;

[0039] A certain proportion of ferric sulfate powder, Variquat CC 42NS, and a light-curable resin are mixed, stirred, and ground to obtain a resin, and the resin is used for printing; after printing, the printed structure is removed from the printing platform, ultrasonically cleaned for multiple times, and dried at room temperature to obtain a ferric sulfate substrate;

[0040] Step 2: The nickel sulfate template / iron sulfate substrate in step 1 is placed in a muffle furnace (Carbolite AAF1700) for sintering. After that, the degreased nickel oxide structure / iron oxide structure is subsequently transferred to a PECVD furnace and heated and reduced in an argon-hydrogen mixed atmosphere to obtain a 3D printed metal nickel structure.

[0041] Step 3: Dissolve a certain amount of cobalt nitrate hexahydrate, nickel nitrate hexahydrate and hexamethylenetetramine in methanol and stir to form a transparent pink solution. Transfer the solution to an autoclave lined with polytetrafluoroethylene, use aramid wire to suspend the 3D printed metal nickel sample obtained in step 2 in the solution, and heat it to synthesize Ni-Co LDH. Wash it several times with deionized water and dry it in a vacuum oven to obtain Ni-Co LDH@3DNi;

[0042] Step 4: Add a certain amount of sodium sulfide nonahydrate to deionized water and stir until transparent. Then put the Ni-Co LDH@3DNi sample prepared in step 3 into the above solution. Subsequently, transfer the mixture to a 50mL polytetrafluoroethylene-lined autoclave and heat the reaction. Take out the product, wash it with deionized water, and dry it to obtain a NiCo2S4@3DNi electrode;

[0043] Step 5: Mix a certain amount of sodium hydroxide, ammonium persulfate, deionized water and ammonium fluoride solution and transfer them to a 50 mL polytetrafluoroethylene-lined autoclave. * 3 * The 1.44 mm 3D metallic iron substrate was immersed in the solution in an autoclave. After heating for reaction, it was taken out, rinsed with deionized water and dried in a vacuum oven. The prepared substrate was heated and kept in an Ar atmosphere to obtain a Fe2O3@3DFe electrode.

[0044] Step 6: Assemble and prepare an aqueous nickel-iron battery using Fe2O3@3DFe as the positive electrode, NiCo2S4@3DNi as the negative electrode, and 6M potassium hydroxide as the electrolyte.

[0045] Preferably, in step 1, 20-60 g of metal salt, 1-10 mL of Variquat CC 42NS, and 30 mL of photocurable resin (prepared with E-HDDA and E-TMPTA in a ratio of 3:22 and 2 wt.% TPO) are mixed in an amber bottle, stirred at room temperature in a magnetic stirrer for 1-3 hours, and then ground in a planetary ball mill.

[0046] Preferably, in step 2, the degreasing sintering process has a sintering temperature of 200-1000° C. and a sintering time of 1-5 hours. The reduction step is performed in an argon-hydrogen mixed atmosphere at 400-900° C. for 1-5 hours.

[0047] Preferably: in step 3, cobalt nitrate hexahydrate is 0.03-0.1g, nickel nitrate hexahydrate is 0.01-0.5g, hexamethylenetetramine is 0.05-0.1g, and methanol is 20-50mL; the autoclave temperature is 150-200°C, and the reaction time is 10-20 hours; the vacuum drying temperature is 40-80°C, and the time is 10-20 hours.

[0048] Preferably: in step 4, sodium sulfide nonahydrate is 0.5-1.0 g, deionized water is 10-50 mL, the autoclave temperature is 100-150° C., the reaction time is 5-10 hours, the drying temperature is 40-80° C., and the time is 10-20 hours.

[0049] Preferably: in step five, sodium hydroxide is 0.1-0.5 g, ammonium persulfate is 0.2-0.6 g, deionized water is 10-40 mL, 50 mM ammonium fluoride solution is 1.0-6.0 mL, the autoclave temperature is 100-200 ° C, the reaction time is 10-20 hours, the vacuum drying temperature is 200-400 ° C (1 ° C / min heating rate) and maintained in Ar atmosphere for 2-6 hours.

[0050] Preferably: in step six, the Fe2O3@3DFe and NiCo2S4@3DNi electrodes are immersed in an electrolyte, placed at room temperature, assembled face to face and immersed in the solution to assemble and prepare an aqueous nickel-iron battery.

[0051] Example:

[0052] 1. Preparation of 3D printed nickel metal substrate. 58g nickel sulfate powder, 5mL Variquat CC 42NS and 30mL photocurable resin (composed of E-HDDA and E-TMPTA in a ratio of 3:22, TPO is 2wt.%) are mixed and then stirred at room temperature for 1-3 hours, and then ground with a planetary ball mill to make the nickel sulfate powder in the resin finer. After that, it is printed out using digital light processing (DLP) technology to obtain a 3D printed nickel sulfate substrate. Then, degreasing and sintering in a muffle furnace (at 200, 400, and 600°C for 2 hours, and at 840 and 1000°C for 3 hours). After that, the degreased nickel oxide structure is subsequently transferred to a PECVD furnace and reduced in an argon-hydrogen mixed atmosphere at 600°C for 10 hours to obtain a 3D printed nickel metal structure.

[0053] 2. Preparation of NiCo2S4@3DNi electrode. First, Ni-Co LDH was prepared. 0.036g of cobalt nitrate hexahydrate, 0.018g of nickel nitrate hexahydrate, and 0.075g of hexamethylenetetramine were dissolved in 30mL of methanol and stirred to form a transparent pink solution, which was transferred to an autoclave lined with polytetrafluoroethylene. In order to make the active material grow more uniformly, the sample was suspended in the solution using aramid wire. After heating at 180°C for 12 hours, Ni-Co LDH was synthesized, and then washed with deionized water several times and dried in a vacuum oven at 60°C for 12 hours. Then NiCo2S4@3DNi was prepared. 0.70g of sodium sulfide nonahydrate was added to 30mL of deionized water and stirred to form a transparent solution, and then the prepared Ni-Co LDH@3DNi sample was placed in the above solution, and then transferred to a 50mL polytetrafluoroethylene-lined autoclave and reacted at 120°C for 8 hours. Finally, the product was taken out, washed with deionized water, and dried at 60 °C for 12 h to obtain NiCo2S4@3DNi.

[0054] 3. Preparation of 3D printed metal iron substrate. 56g of iron sulfate powder, 5mL of Variquat CC 42NS and 30mL of photocurable resin (composed of E-HDDA and E-TMPTA in a ratio of 3:22, TPO is 2wt.%) were mixed and then stirred at room temperature for 1-3 hours, and then ground with a planetary ball mill to make the iron sulfate powder in the resin finer. After that, it was printed out using digital light processing (DLP) technology to obtain a 3D printed iron sulfate substrate. Then, degreasing and sintering were performed in a muffle furnace (at 200°C for 3 hours, 400°C, 480°C, 600°C for 6 hours, and 800°C for two hours). After that, the degreased iron oxide structure was subsequently transferred to a PECVD furnace and reduced in an argon-hydrogen mixed atmosphere at 800°C for 10 hours to obtain a 3D printed metal iron structure.

[0055] 4. Prepare Fe2O3@3DFe electrode. Mix 0.2g sodium hydroxide, 0.457g ammonium persulfate, 27mL deionized water and 3.0mL 50mM ammonium fluoride solution, then transfer the solution to a 50mL polytetrafluoroethylene-lined autoclave and immerse the 3D metal nickel substrate in the solution in the autoclave. React at 180°C for 12 hours, take out the substrate covered with brick-red ferric oxide, rinse with deionized water and dry in a vacuum oven. Heat the prepared substrate to 350°C (at a heating rate of 1°C / min) and keep it in an Ar atmosphere for 4 hours.

[0056] 5. The fourth step is to assemble an aqueous nickel-iron battery. With Fe2O3@3DFe as the positive electrode, NiCo2S4@3DNi as the negative electrode, and 6M potassium hydroxide as the electrolyte, the Fe2O3@3DFe and NiCo2S4@3DNi electrodes are immersed in the electrolyte, placed at room temperature, assembled face to face and immersed in the solution to obtain an aqueous nickel-iron battery.

[0057] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A method for preparing an aqueous nickel-iron battery, characterized in that The specific steps are as follows: Step 1: Design the F-KS structure template through software; A certain proportion of nickel sulfate powder, Variquat CC 42 NS, and a light-curable resin are mixed, stirred, and ground to obtain a resin, and the resin is used for printing; After printing is completed, the printed structure is removed from the printing platform, ultrasonically cleaned multiple times, and dried at room temperature to obtain a nickel sulfate template; A certain proportion of ferric sulfate powder, Variquat CC 42 NS, and a light-curable resin are mixed, stirred, and ground to obtain a resin, and the resin is used for printing; After printing is completed, the printed structure is removed from the printing platform, ultrasonically cleaned multiple times, and then dried at room temperature to obtain an iron sulfate substrate; Step 2: The nickel sulfate template / iron sulfate substrate obtained in step 1 is placed in a muffle furnace for degreasing and sintering, and the degreased nickel oxide structure / iron oxide structure is then transferred to a PECVD furnace and heated and reduced in an argon-hydrogen mixed atmosphere to obtain a 3D printed metal nickel structure / 3D printed metal iron structure; Step 3: Dissolve a certain amount of cobalt nitrate hexahydrate, nickel nitrate hexahydrate and hexamethylenetetramine in methanol and stir to form a transparent pink solution; transfer the solution to an autoclave lined with polytetrafluoroethylene, and then suspend the 3D printed metal nickel structure obtained in step 2 in the solution, and heat it to synthesize Ni-Co LDH; then wash it with deionized water several times and dry it in a vacuum oven to obtain Ni-Co LDH@3DNi; Step 4: Add a certain amount of sodium sulfide nonahydrate into deionized water and stir until transparent; then put the Ni-Co LDH@3DNi sample prepared in step 3 into the above transparent solution to obtain a mixture; then, transfer the obtained mixture to an autoclave lined with polytetrafluoroethylene, heat the reaction, take out the product, wash it with deionized water, and dry it to obtain a NiCo2S4@3DNi electrode; Step 5: Mix a certain amount of sodium hydroxide, ammonium persulfate, deionized water and ammonium fluoride solution, and transfer them to an autoclave lined with polytetrafluoroethylene; immerse the 3D printed metal iron structure in the solution of the autoclave in this step; take it out after heating reaction, rinse it with deionized water and dry it in a vacuum oven; heat the prepared substrate and keep it in an Ar atmosphere to obtain a Fe2O3@3DFe electrode; Step 6: Immerse the Fe2O3@3DFe and NiCo2S4@3DNi electrodes in an electrolyte with 6 M potassium hydroxide as the electrolyte, and assemble an aqueous nickel-iron battery.

2. The method for preparing an aqueous nickel-iron battery according to claim 1, characterized in that: In the step 1, 20-60 g of metal salt, 1-10 mL of Variquat CC 42 NS, and 30 mL of photocurable resin are mixed in an amber bottle, stirred for 1-3 hours at room temperature using a magnetic stirrer, and then ground using a planetary ball mill; the photocurable resin is prepared by mixing E-HDDA and E-TMPTA in a ratio of 3:22 and adding 2 wt.% TPO.

3. The method for preparing an aqueous nickel-iron battery according to claim 1, characterized in that: In the step 2, the sintering temperature of the degreasing sintering process is 200-1000° C., and the sintering time is 1-5 hours; the reduction step is to reduce in an argon-hydrogen mixed atmosphere at 400-900° C. for 1-5 hours.

4. The method for preparing an aqueous nickel-iron battery according to claim 1, characterized in that: In the step 3, the amount of cobalt nitrate hexahydrate is 0.03-0.1 g, the amount of nickel nitrate hexahydrate is 0.01-0.5 g, the amount of hexamethylenetetramine is 0.05-0.1 g, and the amount of methanol is 20-50 mL; the temperature of the autoclave is 150-200° C., and the reaction time is 10-20 hours; the temperature of the vacuum drying is 40-80° C., and the reaction time is 10-20 hours.

5. The method for preparing an aqueous nickel-iron battery according to claim 1, characterized in that: In the step 4, the amount of sodium sulfide nonahydrate is 0.5-1.0 g, the amount of deionized water is 10-50 mL, the temperature of the autoclave is 100-150° C., the reaction time is 5-10 hours, the drying temperature is 40-80° C., and the reaction time is 10-20 hours.

6. The method for preparing an aqueous nickel-iron battery according to claim 1, characterized in that: In the step 5, the sodium hydroxide is 0.1-0.5 g, the ammonium persulfate is 0.2-0.6 g, the deionized water is 10-40 mL, the 50 mM ammonium fluoride solution is 1.0-6.0 mL, the autoclave temperature is 100-200° C., the reaction time is 10-20 hours, the vacuum drying temperature is 200-400° C., the heating rate is 1° C. / min, and it is maintained in an Ar atmosphere for 2-6 hours.

7. The method for preparing an aqueous nickel-iron battery according to claim 1, characterized in that: In the step six, the batteries are placed at room temperature, assembled face to face and immersed in a solution to assemble an aqueous nickel-iron battery.